Primary anatomic reconstruction in upper and lower lips: case report - Hadad, Henrique; Jesus, Laís Kawamata de; Santos, Ana Flávia Piquera; Capalbo-Silva, Rodrigo; Mendes, Bruno Coelho; Reis, Breno Fernandes dos; Mulinari-Santos, Gabriel; Souza, Francisley Ávila de (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Extensive lip injuries reconstructions require a strategy of treatment. First, the strategy can follow the anatomical references in order to closure the injury reestablishing the lip functions. This article report a reconstruction of an extensive lip injury after a convulsion and a fall in height in a male patient. The lip reconstruction by anatomical reconstruction was effective for immediate structural maintenance and allowed a favorable healing for the second surgical stage. Descriptors: Lip; Wounds and Injuries; Surgery, Oral. References Matin MB, Dillon J. Lip reconstruction. Oral Maxillofac Surg Clin North Am. 2014;26(3):335-57. Lubek JE, Ord RA. Lip reconstruction. Oral Maxillofac Surg Clin North Am. 2013;25(2):103-14. Cakmak MA, Cinal H, Barin EZ, Sakat MS, Karaduman H, Tan O. Total lower lip. reconstruction with functional gracilis free muscle flap. J Craniofac Surg. 2018;29(3):735-37. Larrabee YC, Moyer JS. Reconstruction of mohs defects of the lips and chin. Facial Plast Surg Clin North Am. 2017;25(3):427-42. Coppit GL, Lin DT, Burkey BB. Current concepts in lip reconstruction. Curr Opin Otolaryngol Head Neck Surg. 2004;12(4):281-87. Daraei P, Calligas JP, Katz E, Etra JW, Sethna AB. Reconstruction of upper lip avulsion after dog bite: case report and review of literature. Am J Otolaryngol. 2014;35(2):219-25. Sanniec KJ, Carboy JA, Thornton JF. Simplifying Lip Reconstruction: An Algorithmic Approach. In Semin Plast Surg. 2018;32(2):69-74. Neligan PC. Strategies in lip reconstruction. Clin Plast Surg. 2009;36(3):477-85. Bai S, Li RW, Xu ZF, Duan WY, Liu FY, Sun CF. Total and near-total lower lip reconstruction: 20 years experience. J Craniomaxillofac Surg. 2015;43(3):367-72. Ogawa R. Surgery for scar revision and reduction: from primary closure to flap surgery. Burns Trauma. 2019;7:7 doi: 10.1186/s41038-019-0144-5. Siqueira EJ, Alvarez GS, Laitano FF, Martins PDE, Oliveira MP. Estratégias em reconstrução do lábio inferior. Rev Bras Cir Plást.2012;27(4):536-41. Estlander JA. Eine methode aus der einen lippe substanzverluste der anderen zu erstzen. Arch Klin Chir. 1872;14:622. Reprinted in English in Plast Reconstr Surg. 1968;42:361. Robotti E, Righi B, Carminati M, Ortelli L, Bonfirraro PP, Devalle L et al. Oral commissure reconstruction with orbicularis oris elastic musculomucosal flaps. J Plast Reconstr Aesthet Surg. 2010;63(3):431-39. Yamauchi M, Yotsuyanagi T, Ezoe K, Saito T, Yokoi K, Urushidate S. Estlander flap combined with an extended upper lip flap technique for large defects of lower lip with oral commissure. J Plast Reconstr Aesthet Surg. 2009;62(8):997-1003.